ONE YEAR FOLLOW UP OF POST PERCUTANEOUS TRANSLUMINAL CORONARY ANGIOPLASTY IN PATIENTS OF CORONARY ARTERY DISEASE - SIDDARDHA, SHILIVERI SADHAN; CHIWHANE, ANJALEE; LAHOLE, SWAPNIL; DUBEY, A YUSH (International Journal of Psychosocial Rehabilitation, 2020)
percutaneous coronary intervention is an accepted first-line therapy in acute ST elevation myocardial infarction (STEMI) and ischemia in general population, only limited data is available on outcomes of PTCA patients. Our aim is to follow up patients with myocardial infarction who underwent PTCA for one year. patients who have underwent PTCA and one year followup of those patients were taken. All prospective patients who underwent percutaneous transluminal coronary angiography at this teritiary are rural hospital will be entered in the study. These patients will undergo detailed clinical examination with observation on signs of unstable angina and congestive cardiac failure. Those patients who died during the study either in the hospital or outside will be considered for mortality data. The patients who died during the study period in the hospital the data will be taken from the admission file and those who died outside the hospital information will be telephonically collected those patients coming for follow up at 3 , 6, and 12 months will be undergoing ECG, 2D echo and x ray chest.Those patients unable to come for follow up will be considered loss to follow up.Patients will be attending cardiology follow up OPD and the reporting of clinical end points will be by the cardiologist.From august 2018 to august 2020, 204 patients underwent PTCA (PTCA group n = 204) .Patients were followed 12 months. Results show mortality in ejection fraction of less than 35%( P = 0.04). Although patients underwent PTCA mortality was more in patients who have LV ejection fraction of